2011
DOI: 10.1186/gb-2011-12-10-r106
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Rhizobium leguminosarumto pea, alfalfa and sugar beet rhizospheres investigated by comparative transcriptomics

Abstract: BackgroundThe rhizosphere is the microbe-rich zone around plant roots and is a key determinant of the biosphere's productivity. Comparative transcriptomics was used to investigate general and plant-specific adaptations during rhizosphere colonization. Rhizobium leguminosarum biovar viciae was grown in the rhizospheres of pea (its legume nodulation host), alfalfa (a non-host legume) and sugar beet (non-legume). Gene expression data were compared to metabolic and transportome maps to understand adaptation to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(209 citation statements)
references
References 35 publications
8
200
1
Order By: Relevance
“…Several studies have addressed the transcriptomics of the rhizosphere (Diehn and Relman, 2001;Mark et al, 2005;Matilla et al, 2007;Ramachandran et al, 2011), but always using a controlled approach with a single bacterium, one or a few plants in sterile substrates or purified root exudates. In this study, we used a metatranscriptomic approach and assessed the whole microbial community associated with willow roots growing in non-sterile soil from a contaminated site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have addressed the transcriptomics of the rhizosphere (Diehn and Relman, 2001;Mark et al, 2005;Matilla et al, 2007;Ramachandran et al, 2011), but always using a controlled approach with a single bacterium, one or a few plants in sterile substrates or purified root exudates. In this study, we used a metatranscriptomic approach and assessed the whole microbial community associated with willow roots growing in non-sterile soil from a contaminated site.…”
Section: Discussionmentioning
confidence: 99%
“…The overall increase in the expression of phosphoenolpyruvate carboxykinase (involved in the rate-controlling step of glucose synthesis; repressed by sugars) and CUT1 transport gene (involved in the transport of oligosaccharides) expression in the rhizosphere and the high expression of organic acid uptake and utilization genes in the contaminated rhizosphere suggest that simple sugars are not the main bacterial carbon source in the rhizosphere of willows. Organic acids were previously reported as the main source of carbon in the rhizosphere of many plants, including poplar (Jones, 1998;Lugtenberg et al, 2001;Naik et al, 2009;Ramachandran et al, 2011).…”
Section: Metatranscriptomics Of the Rhizospherementioning
confidence: 99%
See 1 more Smart Citation
“…There are obviously a large range of Arabidopsis mutants that could be tested in this way, including those involved in immune signaling (18) and root secretion such as ABC exporters (19). The alternative approach will be to use bacteria labeled with inducible fluorescent, luminescent (e.g., lux) (20)(21)(22), or FRET biosensors (23) to monitor root secretion and the bacterial response to roots.…”
mentioning
confidence: 99%
“…Nascimento et al (2013) found better effectiveness of biofertilizers in relation to chemical fungicides to control anthracnose in tomato. Several studies have found satisfactory effects in disease control with the use of biofertilizers in plants such as watermelon, cucumber, pepper, peas and others (Murphy et al 2003;Barra et al, 2009;Ling et al 2011;Ramachandran et al 2011;Aravindi et al 2009). …”
Section: Introductionmentioning
confidence: 99%